2008
DOI: 10.1182/blood-2007-08-108324
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of Mpl marks the transition to lymphoid-primed multipotent progenitors with gradual loss of granulocyte-monocyte potential

Abstract: IntroductionWhereas considerable knowledge has been gained with regard to the identity and roles of extrinsic and intrinsic regulators of blood lineage development, much less is known about the molecular mechanisms regulating lineage commitment of hematopoietic stem cells (HSCs). 1,2 Unraveling the involved molecular determinants and mechanisms of lineage restriction will be facilitated by, and most likely depend on, a more complete understanding of the cellular pathways of the lineage restriction process from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 31 publications
5
34
0
Order By: Relevance
“…on May 9, 2018. by guest www.bloodjournal.org From cells, the LMPPs, coexpressed cell-surface FLT3 and THPO receptor, (THPOR, also called c-Mpl), as previously demonstrated. 36 Notably, although THPOR hi LMPPs, in agreement with previous studies, failed to respond to THPO alone, 26 a potent synergy was observed between FL and THPO in promoting the clonal growth and proliferative burst of THPOR hi LMPPs but not of THPOR neg LMPPs (Figure 4A-B). This interaction between FL and THPO was also seen in preGMPs, but to a smaller degree ( Figure 4C).…”
Section: Mice Double Deficient In Fl and Thpo Demonstrate A Role Of Fsupporting
confidence: 87%
“…on May 9, 2018. by guest www.bloodjournal.org From cells, the LMPPs, coexpressed cell-surface FLT3 and THPO receptor, (THPOR, also called c-Mpl), as previously demonstrated. 36 Notably, although THPOR hi LMPPs, in agreement with previous studies, failed to respond to THPO alone, 26 a potent synergy was observed between FL and THPO in promoting the clonal growth and proliferative burst of THPOR hi LMPPs but not of THPOR neg LMPPs (Figure 4A-B). This interaction between FL and THPO was also seen in preGMPs, but to a smaller degree ( Figure 4C).…”
Section: Mice Double Deficient In Fl and Thpo Demonstrate A Role Of Fsupporting
confidence: 87%
“…1,2 In further support of the lymphoid commitment pathway sustaining GM (but not MkE) potential, the earliest thymic progenitors have combined T and GM potential. 3,4 The existence of adult and fetal GMlymphoid-restricted mouse MPPs has been confirmed through alternative approaches, 2,[5][6][7][8] and recently a similar progenitor was also identified in human hematopoiesis. 9,10 The restriction of mouse LMPPs to the fraction of LIN Ϫ SCA1 ϩ KIT ϩ (LSK) cells with high cell-surface FMS-like tyrosine kinase receptor 3 (FLT3) expression and of long-term self-renewing HSCs to LSK cells lacking detectable cell-surface FLT3 expression [11][12][13] raises the question as to what stage of lineage commitment FLT3 (protein) and Flt3 (mRNA) expression is initiated.…”
Section: Introductionmentioning
confidence: 93%
“…5 For details, see supplemental Methods. The publication costs of this article were defrayed in part by page charge payment.…”
Section: Mke Potentialmentioning
confidence: 99%
“…However, rather than a sudden loss of MegE potential, it is more likely that there is a gradual decrease in the ability to commit to these lineages, coinciding with an increase in lymphoid priming. 39 Thus, in this model, LMPPs mainly give rise to CLPs and GMPs but still exhibit limited MegE potential ( Figure 1C) …”
Section: Recently Wilson Et Almentioning
confidence: 99%